2020
DOI: 10.1126/scitranslmed.abb3774
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 poly(GR) aggregation induces TDP-43 proteinopathy

Abstract: TAR DNA-binding protein 43 (TDP-43) inclusions are a pathological hallmark of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS), including cases caused by G4C2 repeat expansions in the C9orf72 gene (c9FTD/ALS). Providing mechanistic insight into the link between C9orf72 mutations and TDP-43 pathology, we demonstrated that a glycine-arginine repeat protein [poly(GR)] translated from expanded G4C2 repeats was sufficient to promote aggregation of endogenous TDP-43. In particular, toxic poly(GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 50 publications
8
131
1
Order By: Relevance
“…Future studies will also need to evaluate mitochondrial transcriptional status in non-C9orf72 cases, including sporadic ALS, as well as in other forms of motor neuron disease, such as spinal muscular atrophy [14], to begin to address whether our findings are directly related to C9orf72 pathogenic mechanisms, such as dipeptide repeat proteins and/ or due to, for example, TDP-43 aggregation. Indeed, recent findings show that C9orf72 dipeptide repeat proteins can lead to cytoplasmic TDP-43 aggregation [24,99]. Thus, does TDP-43 pathology, observed in the vast majority of ALS cases, including C9orf72 [4,72], modulate mitochondrial homeostasis by regulating the processing of mitochondrial transcripts [46]?…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will also need to evaluate mitochondrial transcriptional status in non-C9orf72 cases, including sporadic ALS, as well as in other forms of motor neuron disease, such as spinal muscular atrophy [14], to begin to address whether our findings are directly related to C9orf72 pathogenic mechanisms, such as dipeptide repeat proteins and/ or due to, for example, TDP-43 aggregation. Indeed, recent findings show that C9orf72 dipeptide repeat proteins can lead to cytoplasmic TDP-43 aggregation [24,99]. Thus, does TDP-43 pathology, observed in the vast majority of ALS cases, including C9orf72 [4,72], modulate mitochondrial homeostasis by regulating the processing of mitochondrial transcripts [46]?…”
Section: Discussionmentioning
confidence: 99%
“…Previous work indicated that GR perturbs SG dynamics, thus GR:G3BP1:TDP-43:Nup62 assemblies are likely the result of pathogenic assemblies formed through aberrant liquid-liquid phase separation to promote TDP-43 aggregation 53 . This conclusion is supported by recent work where GFP-(GR)200 promotes the cytoplasmic mislocalization of a transiently expressed TDP-43-Myc protein in vitro and that (GR)20 is sufficient to the drive aberrant phase separation and aggregation of purified TDP-43 in vitro 118 .…”
Section: Discussionmentioning
confidence: 53%
“…In particular, arginine-rich DRPs comprised of glycine-arginine (polyGR) or proline-arginine (polyPR), have consistently been demonstrated to be toxic in experimental systems (Freibaum and Taylor, 2017). Toxicity of polyGR/PR has been observed in cell culture systems (Mori et al, 2013;Kwon et al, 2014;Kramer et al, 2018), in Drosophila models (Mizielinska et al, 2014;Wen et al, 2014), and in mouse models (Zhang et al, 2018;Choi et al, 2019;Cook et al, 2020). We also demonstrated consistent and significant cell type and differentiation-specific toxicity of polyGR/PR in cell culture models (Gill et al, 2019).…”
Section: Introductionmentioning
confidence: 54%